Analisa pengaruh Go-Food terhadap penjualan UMKM di Universitas Muhammadiyah Surakarta - Sukardi, Agung Slamet; Rahmawati, Ira Ayuk (Nur Science Institute, 2022)
This study aims to determine how much influence Go-Food has on MSME sales at UMS. This analysis uses the independent variable, namely Go-Food and the dependent variable, namely MSME sales. The sample of this research is SMEs that have been registered with Go-Food, SMEs that have made buying and selling transactions on the Gojek application. And the SMEs studied around UMS were 18 MSME units. The four MSME categories are in the food and beverage sector which consists of chicken, martabak, thai tea and coffee. Data collection was carried out by collecting primary data with observation techniques, documentation, questionnaires, interviews and literature studies. The statistical method uses the Average Test of Two Populations that are Dependent, namely to test the average difference between two groups of data that are dependent or interrelated. The results of this study indicate that the Go-Food variable has a significant effect on the MSME sales variable at UMS.